Predicting local buckling in steel members under cyclic loads: a strain-based approach using the CSM - Chen,Y; Málaga-Chuquitaype,C; Zhou,F; Gardner,L (Engineering Structures, 2025)
A new approach, based on the Continuous Strength Method (CSM), is presented for the prediction of cross-section failure through inelastic local buckling in steel members under cyclic loading. Cross-section local buckling failure is predicted to occur when a prescribed strain limit is reached; the effect of loading history is accounted for by considering the cumulative strain from each loading cycle. The strain limit is related to the cross-section slenderness, which is based on the local buckling behaviour of the full cross-section, rather than the individual plate width-to-thickness ratios, making it suitable for different section profiles (e.g., hollow sections and I-sections). Finite element models are established, validated and used to conduct parametric studies, covering a series of steel grades, a wide range of cross-section slendernesses and various cyclic axial loading protocols. The resulting numerical data sets are employed to develop a means of rationally considering the contribution of both the compressive and tensile strain ranges in each loading cycle to cross-section failure. The suitability of the newly proposed method is verified against experimental results on beam-columns with hollow sections and I-sections under cyclic loading, as well as numerical results. The findings indicate that the cumulative deformation capacity and local buckling failure of steel cross-sections can be accurately predicted using the developed strain-based design method. The method can be applied in the inelastic analysis of structures under seismic loading and in the seismic design of steel cross-sections.